2022
DOI: 10.3390/electronics11223739
|View full text |Cite
|
Sign up to set email alerts
|

N-Beats as an EHG Signal Forecasting Method for Labour Prediction in Full Term Pregnancy

Abstract: The early prediction of onset labour is critical for avoiding the risk of death due to pregnancy delay. Low-income countries often struggle to deliver timely service to pregnant women due to a lack of infrastructure and healthcare facilities, resulting in pregnancy complications and, eventually, death. In this regard, several artificial-intelligence-based methods have been proposed based on the detection of contractions using electrohysterogram (EHG) signals. However, the forecasting of pregnancy contractions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 55 publications
0
1
0
Order By: Relevance
“…The authors reported that N‐BEATS outperformed the M4 forecast competition winner by 3%. Recently, the architecture has gained a number of desirable properties, including being interpretable, applicable without modification to a wide array of target domains (Jossou et al, 2022; Puszkarski et al, 2021; Sbrana et al, 2020; Siddardha et al, 2021), and fast to train.…”
Section: Brief Review Of Related Workmentioning
confidence: 99%
“…The authors reported that N‐BEATS outperformed the M4 forecast competition winner by 3%. Recently, the architecture has gained a number of desirable properties, including being interpretable, applicable without modification to a wide array of target domains (Jossou et al, 2022; Puszkarski et al, 2021; Sbrana et al, 2020; Siddardha et al, 2021), and fast to train.…”
Section: Brief Review Of Related Workmentioning
confidence: 99%
“…In 2021, an important study 26 revealed that over-sampling applied after data partitioning, i.e., partition-synthesis over-sampling approach, needs to be applied to achieve realistic classification performance, and realistic preterm birth prediction in the case of imbalanced sets. Recently, many interesting studies related to preterm birth prediction using the TPEHG DB were published using traditional feature engineering 27 33 and deep learning 34 37 approaches. A nice review of the literature dealing with the use of EHG records for the task of predicting premature birth and for understanding the underlying physiological processes during pregnancy can be found in 38 .…”
Section: Background and Summarymentioning
confidence: 99%